SUBJECT AND IDENTITY IN BUTLER AND LACLAU: REFLECTION ON THE GENDER DISCOURSE OF ENFOC/PE (Interdisciplinary Studies Journal, 2025)
This article is an excerpt from the theoretical discussion of an ongoing doctoral thesis. Grounded in the post-structuralist field of authors Judith Butler and Ernesto Laclau, the object of study is the educational role developed in gender identities by the National Confederation of Agricultural Workers (CONTAG), based on the training pathways carried out by ENFOC/PE (CONTAG’s National Training School).The epistemic framework undertakes a critique of the metaphysics of the subject, destabilizing the structure of identities and leading to the deconstruction of gender beyond heterobinary primacy. Thus, we propose to problematize what the “being” of gender would be, from the perspective that its political dimension may hold meaning outside metaphysical logic.
Keywords: Gender; Education; Identity